Detection of the novel IL-1 family cytokines by QAH-IL1F-1 assay in rheumatoid arthritis - Wang, M; Wang, B; Ma, Z; Sun, X; Tang, Y; Li, X; Wu, X (Cellular and Molecular Biology, 2016)
The interleukin (IL)-1 family of cytokines comprises 11 members, including 7 pro-inflammatory cytokines (IL-1Î±, IL-1Î², IL-18, IL-33, IL-36Î±, IL-36Î²,IL-36Î³) and 4 anti-inflammatory cytokines (IL-1R antagonist (IL-1Ra), IL-36Ra, IL-37 and IL-38), and play central roles in mediating immune responses. In this study, we detected serum levels of IL-36 subfamily cytokines (including IL-36Î±, IL-36Î², IL-36Î³, IL-36Ra and IL-38), IL-37, IL-33 and aimed to investigate the roles of these cytokines in rheumatoid arthritis (RA) preliminarily. A total of 10 RA patients and 10 healthy controls (HCs) were involved in this study, we measured IL-36 subfamily cytokines, IL-37 and IL-33 levels in the serum of the experiment subjects by QAH-IL1F-1 assay. Clinical and laboratory data of the subjects were collected and analyzed by Spearman's rank test. Compared to that of HCs, IL-36Î±, IL-36Î², IL-36Ra, IL-38 and IL-33 levels were significantly increased in RA patients. We also found RA patients with elevated IL-36Ra had a higher ESR and RF-IgM, and there was a positive correlation between increased IL-36Î± and CRP. Our study suggests that parts of the novel members of IL-1 family cytokines were involved in the pathogenesis of RA, and may provide a novel target for therapies of RA.